A High‐Temperature Na‐Ion Battery: Boosting the Rate Capability and Cycle Life by Structure Engineering. Issue 7 (29th January 2020) - Zhou, Yanping; Zhang, Xianghua; Liu, Yanjing; Xie, Xinxin; Rui, Xianhong; Zhang, Xiong; Feng, Yuezhan; Zhang, Xiaojun; Yu, Yan; Huang, Kama
Abstract: High‐temperature sodium ion batteries (SIBs) have drawn significant heed recently for large‐scale energy storage. Yet, conventional SIBs are in the depths of inferior charge/discharge efficiency and cyclability at elevated temperatures. Rational structure design is highly desirable. Hence, a 3D hierarchical flower architecture self‐assembled by carbon‐coated Na3 V2 (PO4 )3 (NVP) nanosheets (NVP@C‐NS‐FL) is fabricated via a microwave‐assisted glycerol‐mediated hydrothermal reaction combined with a post heat‐treatment. The growth mechanism of NVP@C‐NS‐FL is systematically investigated, by forming a microspherical glycerol/polyglycerol‐NVP complex initially and then converting into flower‐like architecture during the subsequent annealing at a low temperature ramping rate. Benefiting from the integrated structure, fast Na + transportation, and highly effective heat transfer, the as‐obtained NVP@C‐NS‐FL exhibits an excellent high‐temperature SIB performance, e.g., 65 mAh g −1 (100 C) after 1000 cycles under 60 °C. When coupled with NaTi2 (PO4 )3 anode, the full cell can still display superior power capability of 1.4 kW kg −1 and long‐term cyclability (2000 cycles) under 60 °C. Abstract : A 3D hierarchical flower architecture self‐assembled by carbon‐coated Na3 V2 (PO4 )3 (NVP) nanosheets (NVP@C‐NS‐FL) is fabricated. Benefiting from the integrated structure, fast Na + transportation and highly effective heat transfer, the as‐obtained NVP@C‐NS‐FL cathode exhibits an excellent high‐temperature electrochemical performance for sodium‐ion half/full batteries.